Strengthening of high entropy alloys by dilute solute additions: CoCrFeNiAlx and CoCrFeNiMnAlx alloys. (September 2017) - Varvenne, Céline; Curtin, William A.
Abstract: A theory to predict the initial flow stress of an arbitrary N -component fcc random alloy is extended to predict the additional strengthening when a dilute concentration of a substitutional element is introduced. Assuming properties for the N -component alloy to be established, the theory requires only information on the elastic and lattice constants of the new N  + 1-alloy, and makes a parameter-free prediction for the strength-increment due to the added N  + 1st element. The theory is applied to the CoCrFeNiAl x and CoCrFeNiMnAl x systems, achieving good agreement with experiments. The theory thus serves as a valuable tool for guiding design of new fcc random alloys. Graphical abstract: